The Exercise of Experiential Rural Tourism in the Population Nucleus of an Andean Community in Peru - Mamani-Flores, Adderly; Apaza-Ticona, Jorge; Calatayud-Mendoza, Alfredo Pelayo; Calderón-Torres, Alfredo; Maquera-Maquera, Yuselino; Velasquez-Sagua, Hector Luciano; Flores-Chambilla, Salvador Gerardo (Journal of Ecohumanism, 2024)
Experiential rural tourism requires the direct involvement of the local population and tourists. The purpose of the study was to detail and examine the progress and experiences of the implementation of this type of tourism. The elements studied include communication, mutual respect, socio-economic growth, cultural authenticity, shared cultural customs, reciprocity, appreciation of cultural identity and environment; as well as the perceptions and experiences of visitors and local inhabitants. The method used was qualitative, complemented with techniques such as detailed interviews with the local population and visitors, participant observation in the performance of this activity and content study. The outcome shows the complexity of this practice, underlining the relevance of a collaborative and participatory approach that ensures fairness, mutual respect and long-term sustainability for visitors and local inhabitants. Likewise, challenges and tensions linked to power, representation, authenticity and cultural integration are recognized, with the aim of optimizing the distribution of economic benefits for a more inclusive and responsible tourism.